Design and analysis of outdoor and indoor free-space optical communication systems - Wang, Zixiong. (2013)
Free space optical (FSO) communication provides an interesting approach to access networks in both outdoor and indoor situations. For outdoor FSO communication, the system performance is deteriorated by atmosphere attenuation, beam wander and scintillation, where this thesis focuses on the methods to mitigate the adverse effect of scintillation. For the indoor FSO communication, this work is concentrated on visible light communication (VLC), where the system performance is highly associated with the locations of the light-emitting diode (LED) lamp and the receiver. The main objective of the thesis is to investigate and develop novel transmission and detection techniques to improve the performances of both indoor and outdoor FSO communication systems.